Nothing but the truth - Kerwshaw, George (Cambridge English readers, 1999)
Hu is a teenage student at an international school in the exciting city of Bangkok. She has a problem with one of the teachers and does not know what to do. An adventure in a national park, acting in a musical , and the help of friends make Hu realise that she must tell nothing but the truth